(3eBKQ GdEfGaI aj eYGde GdNdGaIs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdNdGaI GdOGhOjI HCeGegG GdCYXe KGHJI GdbhGYO s
(3Cdag CMO YdeGA eUQ ai GdbQf GdJGSY Yf GdNdGaI GdYHGSjI GdJi GfJbdJ deUQ ai OhdI GdeeGdjc hcGf GdeDda ai YgO GdNdjaI GdefJUQ HGddg CHj GdaJM OGhO hCdag HQSe NRGfJgs
(3hQJHg Ydi SHYI CHhGH hNGJeIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdSjGSI hGdGLJeGYs